Towards life cycle sustainability management - Finkbeiner, Matthias (Springer Netherlands, 2011)
Our global society has undergone a paradigm shift from environmental protection towards sustainability. To achieve reliable and robust results when assessing sustainability it is vital to apply the principles of comprehensiveness and life cycle perspective. This is where life cycle sustainability assessment (LCSA) and life cycle sustainability management (LCSM) come into play. This book is a selection of the most relevant contributions to the LCM 2011 conference in Berlin. The material explores scientific and practical solutions to incorporating life cycle approaches into strategic and operational decision making. There are several sections addressing methodological topics such as LCSM approaches, methods and tools, while more application-oriented sections deal with the implementation of these approaches in relevant industrial sectors including agriculture and food, packaging, energy, electronics and ICT, and mobility.